Immunogenicity characterization of mononucleated cells originated from umbillical cord blood (Medical Journal of Indonesia, 2010)
Aim Umbilical cord blood mononucleated (UCBMC) cells has been shown to be the stem cells originated from umbilical cord blood. To date, UCBMC has been introduced as an alternative source for stem cells used in autologous and allogeneic transplantations. Several clinical studies have demonstrated that UCBMCs required less stringent selection for HLA matches between donor and recipient with less cases of graft versus host reaction. In this study, UCBMCs are known to contain many stem cells, were characterized and compared to peripheral blood for their immunogenic profile. Methods To elucidate the potential of UCBMC alloreactivity, mixed lymphocyte reaction (MLR) assay was performed. The donor and effectors cells were HLA-typed using PCR method to determine their alloreactivity. Further, to distinguish the level of HLA class I and II expression flowcytometry was done using monoclonal antibodies against those molecules. All the analyse were carried out on UCBMCs and peripheral blood mononucleated cells (PBMCs). Results The result of MLR assay showed that there was less IFN-γ secretion detected in the co-cultured medium in the presence of UCBMCs compared to PBMCs counterpart, indicating less possible rejection of UCBMC. Further, we found that there were only 1-3 alleles of HLA match (out of 8 alleles) among the PBMCs and UCBMCs. By using flowcytometry assay, we could further demonstrate lower HLA Class I expression level with less amount of HLA Class II expressing cells in UCBMC compared to those in PBMCs. Conclusion These findings clearly demonstrate the low immunogenicity of UCBMCs, based on the low level of secreted IFN-γ in the MLR assay, low expression level of HLA Class I, and small population of HLA Class II expressing cells. The outcomes from this study would raise a better understanding in the usage of umbilical cord blood as an alternative source of stem cells for allogeneic transplantation. (Med J Indones 2010; 19:14-20) Keywords: umbilical cord blood, immunogenicity, stem cell